The Construction of Hybrid Identity in Julia Alvarez's How the Garcia Girls Lost Their Accents - Nurlaela, Resti Siti (2014)
This research investigates the issue of hybrid identity in Julia Alvarez's novel How the Garcia Girls Lost their Accents (1991). The aim of the research is to identify the ways of hybrid identities of main characters are constructed in the novel and to observe how the main characters manifest their hybrid identities. The research employs the descriptive qualitative method in which the writer describes, interprets and analyzes the text to answer the research question. The concept of hybridity proposed by Homi Bhabha (1994) is used as the theoretical framework to analyze the data. Based on the data analysis, this research finds that hybrid identities of the main characters, the Garcia sisters, are constructed in an-in between space which is categorized into in-between past and present, and in-between Dominican and American cultures. Moreover, the research also finds that the Garcia sisters manifest their hybrid identity in three ways: adopting the American life, embracing American values and preserving Dominican cultures. Keywords: culture, immigrants, hybridity, hybrid identity, postcolonial criticism Penelitian ini meneliti tentang isu identitas hibrid dalam sebuah novel karya Julia Alvarez yang berjudul How the Garcia Girls Lost their Accents (1991). Tujuan dari penelitian ini adalah untuk mengetahui bagaimana identitas hybrid yang dimiliki oleh karakter utama dalam novel tersebut dikonstruksi, dan bagaimana karakter utama menunjukkan identitas hybrid mereka. Penelitian ini menggunakan metode deskriptif kualitatif dimana penulis menjelaskan, menginterpretasikan dan menganalisa teks untuk menjawab pertanyaan penelitian. Konsep hibriditas oleh Homi Bhabha (1994) digunakan sebagai kerangka teori untuk menganalisa data. Berdasarkan analisis data, penelitian ini menemukan bahwa identitas hibrid para karakter utama, Garcia bersaudara, dikonstruksi dalam sebuah ruang in-between atau in-between space, yang kemudian dibagi menjadi in-between masa lalu dan masa sekarang (past and present), dan in-between budaya Amerika dan Dominika. Penelitian ini juga menemukan bahwa para karakter utama menunjukkan identitas hibrid mereka dengan tiga cara yaitu dengan mengadopsi kehidupan Amerika, memeluk nilai-nilai Amerika dan mempertahankan budaya Dominika. Kata kunci: budaya, imigran, hibriditas, identitas hibrid, postcolonial criticism.